2017
DOI: 10.1292/jvms.17-0136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-fat diet and fructose-rich diet on obesity, dyslipidemia and hyperglycemia in the WBN/Kob-<i>Lepr<sup>fa</sup></i> rat, a new model of type 2 diabetes mellitus

Abstract: Obesity and type 2 diabetes mellitus (T2DM) are occurring at epidemic-like rates, and these epidemics appear to have emerged largely from changes in daily diet. In the present study, we compared effects of high-fat diet (HFD) and fructose-rich diet (FRD) in WBN/Kob-Leprfa (WBKDF) rats that spontaneously develop obesity, dyslipidemia and T2DM. After a 4-week feeding of each diet, WBKDF-HFD and WBKDF-FRD rats exhibited aggravated obesity and dyslipidemia compared with WBKDF rats fed standard diet (STD). In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 21 publications
6
38
0
1
Order By: Relevance
“…Pre‐diabetic WBKDF rats fed a standard diet are obese and this may be associated with hyperphagia due to the fa gene . HFD causes diet‐induced obesity in humans and various experimental animals, including WBKDF rats . Accordingly, the obesity that develops in WBKDF‐HFD rats includes genetic obesity and HFD‐induced obesity components.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Pre‐diabetic WBKDF rats fed a standard diet are obese and this may be associated with hyperphagia due to the fa gene . HFD causes diet‐induced obesity in humans and various experimental animals, including WBKDF rats . Accordingly, the obesity that develops in WBKDF‐HFD rats includes genetic obesity and HFD‐induced obesity components.…”
Section: Discussionsupporting
confidence: 93%
“…The availability of useful animal models reflecting human obesity syndrome is crucial in the search for new pharmacological compounds to treat obesity. In the previous study, we developed rat models of human MS by feeding HFD or a fructose‐rich diet (FRD) to WBKDF rats, and showed that WBKDF‐HFD rats developed obesity, dyslipidemia, and especially severe hyperglycemia compared to WBKDF‐FRD rats . To obtain further information on the model as a potential experimental animal model of severe MS, we performed a pharmacological investigation on the effects of liraglutide, which is a currently approved GLP‐1 agonist for the treatment of T2DM and obesity .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 It is concerning that type 2 diabetes (T2DM) is caused by obesity; cases of T2DM are rapidly increasing and may result in a worldwide epidemic. 2,3 Furthermore, hyperglycemia in diabetes ultimately leads to long-term damage and complications, including heart and cardiovascular diseases, tissue damage to the liver and pancreas, diabetic ophthalmopathy and chronic kidney disease. 4 Previous studies demonstrated that the morphological characteristics of diabetic nephropathy (DN) include glomerular hypertrophy, tubular atrophy of the basement, mesangial expansion, membrane thickening, interstitial brosis and arteriolar thickening.…”
Section: Introductionmentioning
confidence: 99%